T-Cell-specific loss of the PI-3-linase p110? catalytic subunit results in enhanced cytokine production and antitumor response (2018)
Class IA phosphatidylinositol 3-kinase (PI3K) catalytic subunits p110? and p110? are targets in cancer therapy expressed at high levels in T lymphocytes. The role of p110? PI3K in normal or pathological immune responses is well established, yet the importance of p110? subunits in T cell-dependent immune responses is not clear. To address this problem, mice with p110? conditionally deleted in CD4+ and CD8+ T lymphocytes (p110??/??T) were used. p110??/??T mice show normal development of T cell subsets, but slightly reduced numbers of CD4+ T cells in the spleen. “In vitro,” TCR/CD3 plus CD28 activation of naive CD4+ and CD8+ p110??/??T T cells showed enhanced effector function, particularly IFN-? secretion, T-bet induction, and Akt, Erk, or P38 activation. Tfh derived from p110??/??T cells also have enhanced responses when compared to normal mice, and IL-2 expanded p110??/??T CD8+ T cells had enhanced levels of LAMP-1 and Granzyme B. By contrast, the expansion of p110??/??T iTreg cells was diminished. Also, p110??/??T mice had enhanced anti-keyhole limpet hemocyanin (KLH) IFN-?, or IL-4 responses and IgG1 and IgG2b anti-KLH antibodies, using CFA or Alum as adjuvant, respectively. When compared to WT mice, p110??/??T mice inoculated with B16.F10 melanoma showed delayed tumor progression. The percentage of CD8+ T lymphocytes was higher and the percentage of Treg cells lower in the spleen of tumor-bearing p110??/??T mice. Also, IFN-? production in tumor antigen-activated spleen cells was enhanced. Thus, PI3K p110? plays a significant role in antigen activation and differentiation of CD4+ and CD8+ T lymphocytes modulating antitumor immunity.